2022
DOI: 10.3390/forensicsci2010017
|View full text |Cite
|
Sign up to set email alerts
|

Post-Mortem Quantitation of Amphetamine in Cadaveric Fluids in Saudi Arabia

Abstract: Amphetamine abuse is a known problem in Saudi Arabia; it is estimated that 40% of drug abusers misuse amphetamines. Here, our aim was to perform an up-to-date epidemiological study of amphetamine-related postmortem cases in Jeddah, Saudi Arabia, in which 235 postmortem cases were included. The largest number of cases was recorded for the groups aged between 31 and 40 years (86 cases) and the lowest number of cases was recorded for the group aged between 61 and 70 years old (5 cases). Amphetamine was co-ingeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The claimed prevalence rates of substance misuse in Islamic nations are influenced by various factors. [ 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The claimed prevalence rates of substance misuse in Islamic nations are influenced by various factors. [ 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the few cases may have been related to the low sample size of heroin users and the prohibition on ethanol intake by law in Saudi Arabia due to religious reasons [ 11 , 60 ]. In contrast, 28% and 13% of heroin cases showed co-ingestion of cannabinoids and amphetamine, respectively, which are more popular drugs in this region [ 25 ]; however, these drugs rarely contribute to death [ 61 , 62 , 63 ]. 6-MAM was detected in BNaF in most cases that tested positive for antemortem ethanol, which is consistent with the results of previous investigations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the United Arab Emirates (50%), Bahrain (28%) have reported significant meth seizures between 2016 and 2020 ( UNODC, 2022 ). This emerging trend is noteworthy in the region, where Captagon® has traditionally been the most abused drug ( Al-Asmari, 2021 , Al-Asmari et al, 2022a , Al-Asmari et al, 2022b ). Furthermore, meth use is on the rise in Saudi Arabia (9%), mainly among amphetamine users, with a significant increase in associated fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies are urgently required to advance forensic toxicology investigations, especially in situations where neither blood nor bodily fluid specimens are accessible. While many studies have reported amphetamine and meth concentrations in various specimens ( Kalasinsky et al, 2001 , Alhazmi et al, 2020 , Al-Asmari et al, 2022a , Al-Asmari et al, 2022b ), none have explored meth concentrations in postmortem putrefied human solid tissues. Saudi Arabia, Middle East and North Africa (MENA) countries experience predominantly hot weather throughout the year, which provides conducive conditions for corpses to decompose.…”
Section: Introductionmentioning
confidence: 99%